ASSESSING THE IMPROVEMENT IN LOGICAL REASONING OF STUDENTS ENROLLED IN “NUMBERS FOR LIFE” COURSE AT MCMASTER UNIVERSITY - Kelly, Michaela (My University, 2023)
To be numerate is to have the ability to understand numbers and be confident with numeric information presented in day-to-day situations. The way numeracy is defined varies between researchers; however, most agree that having skills in numeracy is essential to function in the world. In order to provide students with the opportunity for exposure to basic numeracy skills, McMaster University’s course Math 2UU3 – “Numbers for Life” is offered to non-mathematics major students in second year or above. To measure the effectiveness of this course, and to determine whether students retain the numeracy skills and knowledge acquired in the course, we developed a series of assessments with questions based on content learned throughout the semester. Students were tested three times – once before completing the course, once after completing the course, and once again a year later. This study focuses in on the logical reasoning aspect of numeracy which includes understanding logical structures and being able to work through problems rationally and systematically. The results from the study reveal that students who took the course and participated in completing the given assessments showed improvement with their logical reasoning skills significantly.
Keywords: Mathematics Education; Numeracy; Logical Reasoning